A study of the social perception of technology in public spaces in Alajuela Central Cantón, Costa Rica - Víquez Víquez, Andrés (2019)
The present work makes an analysis of the results of a study of the social perception of technology applied in the public spaces of the central canton of Alajuela, Costa Rica. This study is of a non-probabilistic type, commonly used in exploratory research, which counted with the participation of 122 visitors, 55 women and 67 men, aged between 15 and 79 years, in 6 parks of the central canton of Alajuela, using QGIS tool for the spatial analysis of the data. © 2019 IEEE.